Becoming Oneself: The Central Role of Self-Concordant Goal Selection. (November 2014) - Sheldon, Kennon M.
Pursuing personal goals is an important way that people organize their behavior and mature as individuals. However, because people are typically unaware of their own implicit motivations and potentials, they may pick goals that do not serve them well. This article suggests that "self-concordant" goal selection is a difficult self-perceptual skill, with important ramifications for thriving. Various means of conceptualizing and measuring goal self-concordance are considered. Then, relevant literature is reviewed to show that goal self-concordance, as assessed by a self-determination theory methodology, is predicted by goal/motive fit; that goal self-concordance in turn predicts more persistent goal effort and, thus, better goal attainment over time; and that self-concordant goal selection is enhanced by personality variables and interpersonal contexts that promote accurate self-insight and personal autonomy. Implications for the nature of the self, the causes of personality thriving and growth, and the free will question are considered.